Dual Targeting of Intracellular Pathogenic Bacteria with a Cleavable Conjugate of Kanamycin and an Antibacterial, Cell Penetrating Peptide - Brezden, Anna (J Am Chem Soc, 2016)
Bacterial infection caused by intracellular pathogens, such as Mycobacterium, Salmonella, and Brucella, is a burgeoning global health epidemic that necessitates urgent action. However, the therapeutic value of a number of antibiotics, including aminoglycosides, against intracellular pathogenic bacteria is compromised due to their inability to traverse eukaryotic membranes. To address this significant problem, a cleavable conjugate of the antibiotic kanamycin and a non-membrane lytic, broad-spectrum antimicrobial peptide with efficient mammalian cell penetration, P14LRR, was prepared. This approach allows kanamycin to enter mammalian cells as a conjugate linked via a tether that breaks down in the reducing environment within cells. Potent antimicrobial activity of the P14KanS conjugate was demonstrated in vitro, and this reducible conjugate effectively cleared intracellular pathogenic bacteria within macrophage more potently than a conjugate lacking the disulfide moiety. Notably, successful clearance of Mycobacterium tuberculosis within macrophages was observed with the dual antibiotic conjugate, and Salmonella levels were significantly reduced in an in vivo Caenorhabditis elegans model.